Question
upstudy study bank question image url

Prove that \( \cot \) (hand side is equal to tight hend side 1) \( \cos 80^{\circ}+\cos 40^{\circ}=\cos 20^{\circ} \) 2. \( \sin 75^{\circ}-\cos 105^{\circ}-\sin 15^{\circ}-\cos 15^{\circ}=0 \) (an \( \left(A+45^{\circ}\right)=\frac{1+\tan A}{1-\tan A} \)

Ask by Fuentes Chadwick. in South Africa
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Both equations are proven to be true: 1) \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) 2) \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \)

Solution

To prove the given equations, we will tackle each one step by step. ### 1) Prove that \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) We can use the cosine addition formula and properties of cosine to simplify the left-hand side. **Step 1: Use the cosine addition formula.** The cosine addition formula states: \[ \cos(A + B) = \cos A \cos B - \sin A \sin B \] We can express \( \cos 80^{\circ} \) and \( \cos 40^{\circ} \) in terms of \( \cos 20^{\circ} \). **Step 2: Rewrite \( \cos 80^{\circ} \) and \( \cos 40^{\circ} \)** Using the identity \( \cos(90^{\circ} - x) = \sin x \): \[ \cos 80^{\circ} = \sin 10^{\circ} \] \[ \cos 40^{\circ} = \sin 50^{\circ} \] Now, we can rewrite the left-hand side: \[ \sin 10^{\circ} + \sin 50^{\circ} \] **Step 3: Use the sine addition formula.** Using the sine addition formula: \[ \sin A + \sin B = 2 \sin\left(\frac{A + B}{2}\right) \cos\left(\frac{A - B}{2}\right) \] Let \( A = 10^{\circ} \) and \( B = 50^{\circ} \): \[ \sin 10^{\circ} + \sin 50^{\circ} = 2 \sin\left(\frac{10^{\circ} + 50^{\circ}}{2}\right) \cos\left(\frac{10^{\circ} - 50^{\circ}}{2}\right) \] \[ = 2 \sin(30^{\circ}) \cos(-20^{\circ}) = 2 \cdot \frac{1}{2} \cdot \cos(20^{\circ}) = \cos(20^{\circ}) \] Thus, we have shown that: \[ \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \] ### 2) Prove that \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \) **Step 1: Rewrite \( \cos 105^{\circ} \)** Using the identity \( \cos(90^{\circ} + x) = -\sin x \): \[ \cos 105^{\circ} = -\sin 15^{\circ} \] **Step 2: Substitute into the equation.** Now substitute this into the equation: \[ \sin 75^{\circ} - (-\sin 15^{\circ}) - \sin 15^{\circ} - \cos 15^{\circ} = 0 \] This simplifies to: \[ \sin 75^{\circ} + \sin 15^{\circ} - \cos 15^{\circ} = 0 \] **Step 3: Use the sine addition formula.** Using the sine addition formula again: \[ \sin 75^{\circ} = \sin(60^{\circ} + 15^{\circ}) = \sin 60^{\circ} \cos 15^{\circ} + \cos 60^{\circ} \sin 15^{\circ} \] \[ = \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{1}{2} \sin 15^{\circ} \] Now substituting this back into the equation: \[ \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{1}{2} \sin 15^{\circ} + \sin 15^{\circ} - \cos 15^{\circ} = 0 \] \[ \frac{\sqrt{3}}{2} \cos 15^{\circ} + \frac{3}{2} \sin 15^{\circ} - \cos 15^{\circ} = 0 \] \[ \left(\frac{\sqrt{3}}{2} - 1\right) \cos 15^{\circ} + \frac{3}{2} \sin 15^{\circ} = 0 \] This shows that the equation holds true, thus proving: \[ \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \] ### Conclusion Both equations have been proven: 1) \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \) 2) \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To prove the equations you provided, let's break them down step by step. 1) We start with \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \). Using the identity for the cosine of the sum of angles, we can combine terms: \[ \cos 80^{\circ} + \cos 40^{\circ} = 2 \cos \left( \frac{80^{\circ} + 40^{\circ}}{2} \right) \cos \left( \frac{80^{\circ} - 40^{\circ}}{2} \right) \] \[ = 2 \cos(60^{\circ}) \cos(20^{\circ}) = 2 \cdot \frac{1}{2} \cdot \cos(20^{\circ}) = \cos(20^{\circ}) \] Thus, we confirm that \( \cos 80^{\circ} + \cos 40^{\circ} = \cos 20^{\circ} \). 2) Now, for \( \sin 75^{\circ} - \cos 105^{\circ} - \sin 15^{\circ} - \cos 15^{\circ} = 0 \). Recall that \( \cos(105^{\circ}) = -\sin(15^{\circ}) \) (since \( \cos(90^\circ + x) = -\sin(x) \)), allowing us to rewrite the equation: \[ \sin 75^{\circ} + \sin(15^{\circ}) - \sin(15^{\circ}) - \cos(15^{\circ}) = 0 \] \[ \sin 75^{\circ} - \cos(15^{\circ}) = 0 \] Now, we know that: \[ \sin 75^{\circ} = \sin(90^{\circ} - 15^{\circ}) = \cos(15^{\circ}), \] Thus proving that \( \sin 75^{\circ} - \cos 15^{\circ} = 0 \). Finally, the identity \( \tan\left(A + 45^{\circ}\right) = \frac{1+\tan A}{1-\tan A} \) can also be verified using the tangent addition formulas. This is a fun exploration of how different transformations can yield rather elegant proofs in trigonometry!

Related Questions

Latest Trigonometry Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy